2007
DOI: 10.1265/ehpm.12.272
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Radical Scavenger Protein from Broad Beans on Glutathione Status in Human Lung Fibroblasts

Abstract: Objective: Human diploid cells are more susceptible to oxidative stress at late passage than at early passage, presumably because of the decrease in cellular-reduced glutathione (GSH) concentration. Water-soluble protein (WSP) from broad beans scavenges free radicals. The effects of WSP on the glutathione system were examined in PDL 20 (early passage) and PDL 50 (late passage) human lung fibroblasts (TIG-1).Methods: To determine cytosolic glutathione peroxidase (GSH-Px) activities, glutathione reductase (GR) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…Previously, we published two papers describing the characteristics of broad beans [17,18]. It was found that extracts from the broad beans possess antioxidant and cellular growth properties.…”
Section: Total Phenolic Content Of Ethanol Extracts Of Dried Seedsmentioning
confidence: 99%
“…Previously, we published two papers describing the characteristics of broad beans [17,18]. It was found that extracts from the broad beans possess antioxidant and cellular growth properties.…”
Section: Total Phenolic Content Of Ethanol Extracts Of Dried Seedsmentioning
confidence: 99%